Intramolecular activity regulation of adhesion GPCRs in light of recent structural and evolutionary information - Gunnar Kleinau; Amal Hassan Ali; Franziska Wiechert; Michal Szczepek; Andrea Schmidt; Christian M.T. Spahn; Ines Liebscher; Torsten Schöneberg; Patrick Scheerer (Elsevier, 2023)
The class B2 of GPCRs known as adhesion G protein-coupled receptors (aGPCRs) has come under increasing academic and nonacademic research focus over the past decade due to their physiological importance as mechano-sensors in cell-cell and cell-matrix contexts. A major advance in understanding signal transduction of aGPCRs was achieved by the identification of the so-called Stachel sequence, which acts as an intramolecular agonist at the interface between the N terminus (Nt) and the seven-transmembrane helix domain (7TMD). Distinct extracellular signals received by the Nt are integrated at the Stachel into structural changes of the 7TMD towards an active state conformation. Until recently, little information was available on how the activation process of aGPCRs is realized at the molecular level. In the past three years several structures of the 7TMD plus the Stachel in complex with G proteins have been determined, which provide new insights into the architecture and molecular function of this receptor class. Herein, we review this structural information to extract common and distinct aGPCR features with particular focus on the Stachel binding site within the 7TMD. Our analysis extends the current view of aGPCR activation and exposes similarities and differences not only between diverse aGPCR members, but also compared to other GPCR classes.